Expression of Hsp70, Igf1, and Three Oxidative Stress Biomarkers in Response to Handling and Salt Treatment at Different Water Temperatures in Yellow Perch, Perca flavescens - Eissa, Nour; Wang, Han-Ping; Yao, Hong; Shen, Zhi-Gang; Shaheen, Adel A.; Abou-ElGheit, Elsayed N. (Frontiers in Physiology, 2017)
Stress is a major factor that causes diseases and mortality in the aquaculture industry. The goal was to analyze the expression of stress-related biomarkers in response to different stressors in yellow perch, which is an important aquaculture candidate in North America and highly sensitive to handling in captivity. Three fish groups were established, each having four replicates, and subjected to water temperatures of 14, 20 & 26 ºC and acute handling stress was performed followed by a salt treatment for 144h at a salinity of 5 ppt. Serum and hepatic mRNA levels of heat shock protein (hsp70), insulin-like growth factor 1 (Igf1), glutathione peroxidase (Gpx), superoxide Dismutase 1 (Sod1), and glutathione reductase (Gsr) were quantified at seven times interval over 144 h using ELISA and RT-qPCR. Handling stress caused a signiﬁcant down-regulation in Hsp70, Gpx, Sod1, and Gsr at a water temperature of 20 ºC compared to 14 and 26ºC. Igf1 was significantly upregulated at 20 ºC and down-regulated at 14 and 26ºC. Salt treatment had a transient reverse effect on the targeted biomarkers in all groups at 72 h, then caused up regulation after 144 h, compared to the control groups. The data showed a negative strong regulatory linear relationship between igf1 with hsp70 and anti-oxidative gene expressions. These findings could provide valuable new insights into the stress responses that affect fish health and could be used to monitor the stress.